Peningkatan Pengetahuan Keluarga Dalam Perawatan Pasien Paliatif - Rohman, Asri Aprilia; Rohimah, Siti; Puspita, Bunga; Arzaqi , Reyhan Abel; Nursafitri, Vina (Kolaborasi: Jurnal Pengabdian Masyarakat, 2024)
Introduction: According to WHO data, it is estimated that more than 40 million people need palliative care every year. This includes patients with cancer, heart disease, lung disease, and neurodegenerative diseases such as Alzheimer's disease. Palliative patient care often involves support from the family, and this condition can affect the patient's quality of life as well as the family's own well-being. Many families do not have sufficient knowledge about palliative care, including how to manage symptoms, provide daily care, or understand the patient's emotional needs Objective: Participants in this activity totaled 35 people Method: The method for this community service activity is continuous counseling Result: Based on the training results, data showed that there was an increase in knowledge with the average increase in post-test results being 15.2 with the highest score on the post-test being 98. Conclusion: The conclusion of community service regarding increasing family knowledge in palliative care has succeeded in increasing family understanding and skills in caring for family members who need palliative care. Families now better understand the concept of palliative care, including aspects such as pain management, symptom control, and emotional support. These activities also help reduce the stigma that may exist regarding palliative care and overcome the uncertainty that families often feel. Better knowledge allows families to feel more prepared and confident in carrying out care